Remapping Travel Narratives (1000-1700) To the east and back again - Piera, Montserrat (Arc Humanities Press, 2018)
With a specific focus on travel narratives, this collection looks at how Islamic and eastern cultural threads were weaved, through travel and trading networks, into Western European/Christian visual culture and discourse and, ultimately, into the artistic explosion which has been labeled the "Renaissance." Scholars from across humanities disciplines examine Islamic, Jewish, Spanish, Italian, and English works from a truly comparative and non-parochial perspective, to explore the transfer through travel of cultural and religious values and artistic and scientific practices, from the eleventh to the seventeenth centuries. During this period travel, military conquest and trade through the Mediterranean placed Western European citizens and merchants in contact with Islamic and eastern technology and culture, and travel narratives illustrate the converging and pragmatic dynamics of cultural acceptance. Perhaps the spread of "Renaissance" values and beliefs might have followed a trajectory the reverse of what is generally assumed, and that salient aspects of Renaissance culture traveled from the fringes of Islamic and eastern cultures to the midst of hegemonically Christian polities.